Deposition of indium nitride films by activated reactive evaporation process - a feasibility study - Patil, Sheetal J.; Bodas, Dhananjay S.; Mandale, A. B.; Gangal, S. A. (Applied Surface Science, 2005)
Indium nitride (InN) films are deposited by `activated reactive evaporation (ARE)' process using parallel plate coupled nitrogen plasma (radio frequency source of 13.56 MHz) and evaporation of pure indium powder by resistive heating. Depositions are carried out by varying RF plasma power, on n-type silicon &LANGBRAC; 1 0 0&RANGBRAC; substrate, maintained at room temperature, at a nitrogen gas pressure of 1.06 x 10(-1) Pa (8 x 10 (-4) Torr). The film's crystallinity was examined by X-ray diffraction (XRD) and topography by scanning electron microscope (SEM). The diffraction pattern shows polycrystalline nature of the deposited films with characteristics of hexagonal structure. XRD peak intensity increases with increase in power. SEM observations show a smooth and pinhole free surface having improved quality of film with hexagonal structure as the power is increased from 60 to 120 W. Primary X-ray photoelectron spectroscopy (XPS) results show binding energies of the In 3d levels and N 1s level matching well with that of stoichiometric InN. Further, the refractive index of the films, measured by ellipsometry, is in the range of η = 2.79-2.91 with the variation of plasma power, which is in good agreement with the standard value for indium nitride (η = 2.9). These results indicate the feasibility of using, `activated reactive evaporation (ARE)' process for indium nitride depositions on silicon &LANGBRAC; 1 0 0&RANGBRAC; substrates maintained at room temperature. © 2004 Elsevier B.V. All rights reserved.
Keywords: activated reactive evaporation; ellipsometry; indium nitride; SEM; XRD